From community to Rome: the women in the Gnostic community and the sexual process of segregation among the protoorthodox Christians (I-IV AD) - Silva, Roberta Alexandrina da (Romanitas - Revista de Estudos Grecolatinos, 2015)
Firstly, this article focuses on gender relations in early Christianity, starting from the Pauline communities – it was Paul of Tarsus who defined the Christian theology and identity – in the first decades of the first century. Secondly, we deal with the Gnostic communities until the fourth century. The article aims at analyzing the speeches of femininity and masculinity within the corpus Paulinum, a set of canonical texts, and within the Gnostic texts of Nag Hammadi, considered not canonical ones.